Evaluation of the aphrodisiac activity of Tribulus terrestris Linn. in sexually sluggish male albino rats - Singh, Surender (Medknow Publications & Media Pvt Ltd, 2012)
OBJECTIVES: To study the effect of acute and repeated dose administration of lyophilized aqueous extract of the dried fruits of Tribulus terrestris (LAET) on sexual function in sexually sluggish male albino rats. MATERIALS AND METHODS: Aphrodisiac activity of the test drug was evaluated in terms of exhibited sexual behavior. In order to assess the effect of chronic T. terrestris exposure on the hypothalamus--pituitary--gonadal axis, testosterone level estimation and sperm count were carried out. Twenty-eight-day oral toxicity studies were carried out to evaluate the long-term effects of the LAET administration on different body systems. RESULTS: A dose-dependent improvement in sexual behavior was observed with the LAET treatment as characterized by an increase in mount frequency, intromission frequency, and penile erection index, as well as a decrease in mount latency, intromission latency, and ejaculatory latency. The enhancement of sexual behavior was more prominent on chronic administration of LAET. Chronic administration of LAET produced a significant increase in serum testosterone levels with no significant effect on the sperm count. No overt body system dysfunctions were observed in 28-day oral toxicity study. CONCLUSIONS: Findings of the present study validate the traditional use of T. terrestris as a sexual enhancer in the management of sexual dysfunction in males.